Analysis Of The Utilization Of Used Plastic Bottles As Trash Cans - Retno Ayu Indah K (Abdimas Paspama, 2024)
Plastic waste is an example of inorganic waste whose use is so large that it requires treatment so that its presence does not have a negative impact on the environment, such as accumulation of waste, resulting in environmental pollution. Anticipatory and preventive steps are needed to overcome this problem, one of the appropriate strategies is 3R Reduce, Reuse and Recycle, which we should apply in dealing with plastic waste. Examples of plastic waste: plastic bottles, glass bottles, plastic bags, etc.Not all places have rubbish disposal facilities. Especially nowadays, rubbish dumps are a necessity, so rubbish dumps are needed. The solution to this problem is to make a trash can from used gallons, which can be made easily, with tools and materials that are easy to obtain. The raw materials used do not cause problems, because inorganic waste is always available every day.